The medical management of Cushing's syndrome. - Morris, D; Grossman, A (2002)
Cushing's syndrome results from prolonged exposure to excessive circulating glucocorticosteroids, and is associated with significant morbidity and mortality. While the treatment of choice in most patients is surgical, the metabolic consequences of the syndrome, including increased tissue fragility, poor wound healing, hypertension, and diabetes mellitus, increase the risks of such surgery. The hypercortisolemia and its sequelae can be efficiently reversed using medical therapy, either as a temporary measure prior to definitive treatment, or longer term in more difficult cases. Drug treatment has been targeted at the hypothalamic/pituitary level, the adrenal glands, and also at the glucocorticoid receptor level. In this review we discuss the pharmacotherapeutic agents that have been used in Cushing's syndrome, and their efficacy, the monitoring of treatment, and potential therapies that may prove useful in the future in this complex endocrinological disorder.